Effect of temperature on mechanical properties of Ti-based metallic glass matrix composite. (December 2015) - Wang, Y.S.; Hao, G.J.; Zhang, Y.; Qiao, J.W.; Lin, J.P.
Abstract: Systematic mechanical behaviors were investigated in a Ti-based metallic glass matrix (MGM) composite containing the in-situ β -dendrite phase at 100 K–298 K. We found that the yielding strength increased but the plastic strain decreased with a decrease temperature. The sharp ductile to brittle transition occurred at 100 K. The MGM composite exhibits the large work-hardening behavior at 298 K, but all sample display the work-softening behavior below 298 K. The nominal work-hardening parameter was employed to express the dependence of mechanical properties on temperatures including the brittle failure, the work-hardening and work softening behaviors. It may provide a useful way to evaluate the dependence of mechanical properties on temperatures of MGM composite. Highlights: The yielding strength increased but the strain decreased with a decrease temperature. The sharp ductile to brittle transition occurred at 100 K. The MGM composite exhibits the large work-hardening behavior at 298 K. All sample display the work-softening behavior below 298 K. The nominal work-hardening parameter was employed to express the dependence.